Surface Modification Chemistries of Materials Used in Diagnostic Platforms with Biomolecules - Mukesh Digambar Sonawane; Satish Balasaheb Nimse (Journal of Chemistry)
Biomolecules including DNA, protein, and enzymes are of prime importance in biomedical field. There are several reports on the technologies for the detection of these biomolecules on various diagnostic platforms. It is important to note that the performance of the biosensor is highly dependent on the substrate material used and its meticulous modification for particular applications. Therefore, it is critical to understand the principles of a biosensor to identify the correct substrate material and its surface modification chemistry. The imperative surface modification for the attachment of biomolecules without losing their bioactivity is a key to sensitive detection. Therefore, finding of a modification method which gives minimum damage to the surface as well as biomolecule is highly inevitable. Different surface modification technologies are invented according to the type of a substrate used. Surface modification techniques of the materials used as platforms in the fabrication of biosensors are reviewed in this paper.